1961
DOI: 10.1070/rc1961v030n11abeh003004
|View full text |Cite
|
Sign up to set email alerts
|

Cyanoethylation, Decyanoethylation, and Transcyanoethylation

Abstract: In the long gap between the boiling point of sulphur (444O.60 c.) and the freezing point of gold (1063" c.) there is no fixed point which can conveniently be used for the routine calibration of thermocouples in terms of the International Temperature Scale. The boiling point of selenium (about 690" c.) is suggested as a possible fixed point in this region, and as a first step towards enabling it to be used for this purpose the precise determination of its value has been undertaken.The determination was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…Again, as in reaction 1-6, the rate of reaction with primary amines (specifically EDA) is faster than with NH3. Such transcyanoethylations have been observed in aromatic nitrile reduction (Butskus, 1961), and by Whitmore et al (1944), who observed that VCN reacts with aminopropionitrile approximately 20X faster than with NH3.…”
Section: Resultsmentioning
confidence: 55%
“…Again, as in reaction 1-6, the rate of reaction with primary amines (specifically EDA) is faster than with NH3. Such transcyanoethylations have been observed in aromatic nitrile reduction (Butskus, 1961), and by Whitmore et al (1944), who observed that VCN reacts with aminopropionitrile approximately 20X faster than with NH3.…”
Section: Resultsmentioning
confidence: 55%
“…For large-scale synthesis or to obtain higher integrity DNA products, the phosphorus protective group is removed first with a hindered primary or secondary amine such as tert -butylamine or diethylamine . The amine traps the acrylonitrile byproduct of the β-cyanoethyl protective group and prevents modification to the heterobases. The solid-support linkage is then cleaved along with the heterobase amide protective groups using a more nucleophilic amine, typically ammonia or methylamine under aqueous conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, the role of the catalyst consists in ionization of the benzimidazole NH group of molecule II, which leads to the formation of N-anions subjected to the electrophylic attack of AN molecules. However, the process of N-cyanoethylation, in contrast to the C-cyanoethylation, is reversible [6]. Therefore, the thermodynamically controlled interaction of 2-cyanomethylbenzimidazole (II) with AN involves the following sequence of proc- II 98 60 4t 33 II1 0 19 34 39 VI 0 6 II 15 VII 0 5 5 5 Notes.…”
Section: VIIImentioning
confidence: 99%